Traditional Islam and Modern Atheism According To Mustafa Sabri’s Thought - Surawan; Awang, Sarimah (SHAHIH: Journal of Islamicate Multidisciplinary, 2024)
Mustafa Sabri (1869-1954) was the last Islamic sheikh of the Ottoman Caliphate who adhered to the traditional madhhab, as depicted in his work entitled Mauqif al-'Aql wa al-'Ilm wa al-'Aalam min Rabb al-'Alamin wa Ibadihi al-Mursalin. The central issue in Sabri's work revolves around countering the secularization of the Islamic world, particularly the efforts led by Mustafa Kemal Pasha. This research adopts a library research approach, focusing exclusively on analyzing Sabri's Mauqif al-'Aql wa al-'Ilm wa al-'Aalam min Rabb al-'Alamin wa Ibadihi al-Mursalin as the primary source. The findings of this research reveal that, according to Sabri, religion is the most fundamental principle, one that is unchangeable by anyone. Sabri clearly distinguishes between faith and deeds, emphasizing that Islam is primarily a religion of faith rather than merely one of deeds. This is because, in Sabri's view, a person's faith determines whether their deeds are accepted in religion.